What is implicit culture?. (9th January 2022) - Lizardo, Omar
Abstract: In this paper, I examine what it means for culture, in both its personal and public forms, to be implicit. I begin by considering a recent attempt to develop a descriptive taxonomy of other people's views of practices developed by Stephen Turner. A key result is that a specific combination of claims about the properties of practices yields an ontologically problematic category, which is a candidate for elimination. Following Turner's lead, I provide my own refurbished taxonomy of practical culture that does not contain ontologically problematic members. Another key result of the initial analysis is that implicitness is a relational property presupposing at least one agent with awareness (or unawareness) of the cultural element in question. This epistemic dependence implies that only personal culture internalized by people can be coherently thought of as 'implicit' (to them). Finally, I conclude that using mentalistic versions of implicitness to characterize public culture, such as texts, language, monuments, tools, and classifications on paper, yields the same ontologically incoherent category eliminated in the first step. Following from this, I argue that it is desirable to conceptualize 'implicit' in a way that makes sense for public culture without stirring up the ghosts of collective minds and related conundrums. I propose one such (weak) version of implicitness when speaking of public culture that does not run afoul of this issue. I then return to personal culture, considering whether 'implicitness' is a unitary property of this kind, answering in the negative. This conclusion requires us to develop a principled taxonomy of the distinct ways personal culture can be 'implicit, ' yielding personal culture that is implicit because it acquired 'automatic' status, versus personal culture that is implicit because it lacks (access) consciousness.